Robust and adaptive model predictive control of nonlinear systems - Guay, Martin 1966-; Adetola, Veronica; DeHaan, Darryl (IET control, robotics and sensors series, 2015)
The following topics are dealt with: adaptive control; constrained nonlinear systems; disturbance attenuation; robust adaptive economic MPC; and discrete-time systems.